Social quality : from theory to indicators - Maesen, Laurent van der; Walker, Alan , 1949- (New York : Palgrave Macmillan, 2012)
This collection sets out the latest research on the concept of 'social quality', developing its theoretical foundations and applying it to pressing policy issues such as the future of the European Union and sustainable global development
1. European and global challenges -- 2. Theoretical foundations -- 3. Conceptual location of social quality -- 4. Social quality indicators -- 5. Socio-economic security -- 6. Social cohesion -- 7. Social inclusion -- 8. Social empowerment -- 9. The functions of social quality indicators -- 9. Conclusion : Social quality and sustainability
Includes bibliographical references (p. 275-311) and index
Keywords: Social policy